Single‐phase cuprite thin films prepared by a one‐step low‐vacuum thermal oxidation technique. (6th March 2019) - Du, Wenhan; Yang, Jingjing; Zhang, Keke
Abstract : Cu2 O thin film solar cells have attracted the interest of many researchers owing to their non‐toxic and earth‐abundant properties. High‐quality pure‐phase Cu2 O thin films were prepared by using a simple low‐vacuum thermal annealing technique. The growth temperatures of the Cu2 O thin films were varied from 400 to 1000°C. X‐ray diffraction (XRD) and scanning electron microscopy were used to characterise the structural and morphological changes of the thin films. The XRD results suggested that all the films were pure‐phase Cu2 O; thus, no second‐phase CuO was observed. The detailed evolution of the surface morphology was investigated. The electron dispersion spectrum (EDS) results show that the atomic ratio of Cu and O were changed with the annealing temperature, the ratio change from around 2:1 to 1.84:1 with the turning temperature of 800°C, indicating copper vacancy formed during annealing temperature higher than 800°C. EDS results well matched the d‐spacing changes of the XRD results.